Faith Affiliation, Religiosity, and Attitudes Towards the Environment and Climate Change - Tsimpo, Clarence; Wodon, Quentin (Taylor and Francis, 2016)
Sustainability and environmental issues, including the threat of global warming, are at the core of the recently adopted Sustainable Development Goals. The agreement reached at the 2015 United Nations Climate Change Conference in Paris is encouraging. Yet at the same time, political commitment and a willingness to make sacrifices today for longer-term benefits and the common good are often lacking. Unless decisive actions are taken, global warming is likely to have a major negative impact on populations, leading to, among other things, an increase in extreme weather shocks that can have dramatic effects for populations. The adoption of long-term ethical and spiritual perspectives by religions or religious groups is, in principle, a conducive means to transcending narrow and immediate self-interest.